ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DIMEDIASI KEPUTUSAN PEMBELIANPT. CARRAMICA KREASI INDONESIA PASCAPANDEMI COVID 19 - Lulu Hana Salsabila (2023)
This study analyzes customer satisfaction at PT. Indonesian Creative Carramica. The purpose of this study was to examine the effect of service quality and purchasing decisions on customer satisfaction and to examine the effect of service quality on purchasing decisions. This research is quantitative by distributing questionnaires to 111 Carramica customers. Using the Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) alternative with the Smart-PLS 4.0 program. the results of data analysis show that: (1) Service Quality has a significant effect on Purchasing Decisions of PT. Indonesian Creative Carramica. (2) Service Quality has a significant effect on Customer Satisfaction with PT. Indonesian Creative Carramica. (3) Service Quality has a significant effect on Customer Satisfaction through Purchasing Decisions of PT. Indonesian Creative Carramica.